(The Role, Development and Regulation Of Functional Food) - Dadang Supriatna (Warta Industri Hasil Pertanian, 2006)
Recentlly human daily diet tends to chamges not only to consume the nutrious food product but also the nutrious,safety and healthy effect food.The wrong diet manner and wrong diet life style of someone will emerge the degenerative disease such as diabetes melitus,atherosclerosis,cancer,obesity,coronary heart diseases,osteoporosis etc.Functional foods which have the physiological effect on preventing of the diseases and main taing the health have a prospect to be developed.For protectintg the consumer in using or consuming the functional food,it should be made its regulation.